Hepatoid adenocarcinoma of lung: A diagnostic challenge - Series of six cases with histopathological, predictive molecular and PD.L1 assessment - Sunil Pasricha; Shrruti Grover; Meenakshi Kamboj; Divya Bansal; Ullas Batra; Gurudutt Gupta; Anila Sharma; Garima Durga; Ankush Jajodia; Venkata P B. Koyyala; Anurag Mehta (Wolters Kluwer Medknow Publications, 2021)
Hepatoid adenocarcinoma of lung is a rare entity, accounting for 5% of all hepatoid adenocarcinoma. Distinguishing it from metastatic hepatocellular carcinoma is essential, but occasionally can be very challenging, especially with concurrent liver mass. A judicious immunohistochemical panel is warranted for accurate diagnosis and subsequent preservation of tissue for molecular testing. There is limited data on the mutational status, behavior and management strategies of this type of lung adenocarcinoma. We report largest series of six cases of hepatoid adenocarcinoma of lung citing the clinical, histopathological, immunohistochemical and molecular parameters including PD-L1 immunoexpression as a predictive biomarker for immunotherapy. None of the evaluated cases showed targetable mutation; however, four out of six cases showed significant PD-L1 expression. All the cases presented with advanced stage and received chemotherapy, however overall prognosis was dismal. In view of significant PD-L1 expression in these tumors and poor response to conventional chemotherapy, these cases might be considered for upfront immunotherapy.